Blockade of multidrug resistance associated proteins aggravates acute pancreatitis and blunts atrial natriuretic factor beneficial effect in rats: Role of MRP4/ABCC4 - Ventimiglia, Maria Silvia (2015)
We previously reported that atrial natriuretic factor (ANF) stimulates secretin-evoked cAMP efflux through multidrug resistance-associated protein 4 (MRP4) in the exocrine pancreas. Here we sought to establish in vivo whether this mechanism was involved in acute pancreatitis onset in the rat. Rats pretreated with or without probenecid (MRPs general inhibitor) were infused with secretin alone or with ANF. A set of these animals were given repetitive cerulein injections to induce acute pancreatitis. Plasma amylase and intrapancreatic trypsin activities were measured and histological examination of the pancreas performed. Secretin alone activated trypsinogen but induced no pancreatic histological changes. Blockade by probenecid in secretin-treated rats increased trypsin and also induced vacuolization, a hallmark of acute pancreatitis. ANF prevented the secretin response but in the absence of probenecid. In rats with acute pancreatitis, pretreatment with secretin aggravated the disease, but ANF prevented secretin-induced changes. Blockade of MRPs in rats with acute pancreatitis induced trypsinogen activation and larger cytoplasmic vacuoles as well as larger areas of necrosis and edema that were aggravated by secretin but not prevented by ANF. The temporal resolution of intracellular cAMP levels seems critical in the onset of acute pancreatitis, since secretin-evoked cAMP in a context of MRP inhibition makes the pancreas prone to injury in normal rats and aggravates the onset of acute pancreatitis. Present findings support a protective role for ANF mediated by cAMP extrusion through MRP4 and further suggest that the regulation of MRP4 by ANF would be relevant to maintain pancreatic acinar cell homeostasis.